Tellurium and precious-metal ore minerals at Mina Capillitas, Northwestern Argentina - Marquez Zavalia, Maria Florencia (2004)
Mina Capillitas is an epithermal-type deposit located in Catamarca province of NW Argentina. Six separate stages of mineralization were identified in this complex Cu-Au-S-As-Sb-Pb-Zn association; the native elements (Au and Te) and Te minerals are concentrated in the fourth stage. Gold occurs as small grains with an average fineness of 920, hosted mainly by quartz and coexists with hübnerite and Bi minerals. Tellurium occurs locally in grains up to 10 μm in diameter, and is associated with the Te-bearing minerals of Au, Ag, Bi, Cu, and Ni. These Te minerals include krennerite, calaverite, sylvanite, petzite, hessite, stützite, goldfieldite, melonite, tetradymite, and possibly volynskite. The grains are generally arranged in larger polycrystalline aggregates. These minerals occur in quartz, generally accompanied by hübnerite, pyrite, chalcopyrite, and Bi- and Sn-bearing minerals. The mineralizing fluids cooled gradually with the typical temperatures ranges characteristic of epithermal systems. Based on the preponderance of the different gangue minerals, we suggest that the pH of the environment became progressively more basic after the third stage of mineralization. This mineral assemblage together with the fluid inclusion homogenization temperature data indicate that the log f S2 values declined as the fluids deposited the Te-bearing minerals. The absence of tellurium phases in the first three stages suggests that either the source of the tellurium had not yet been tapped or that the log f Te2 lay below -10 to -17, the minimum activity for the Te phases present in stage IV to form.